Analysis Of Product Quality And Consumer Satisfaction On Purchasing Decisions For Garmin Brand Watches - Sumaya, Sumaya; B, Mesra (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research was conducted at PT Erajaya Swasembada Medan which is engaged in selling Garmin brand watch products. The purpose of this study was to determine the effect of product quality and customer satisfaction on consumer purchasing decisions on Garmin watch products. The population is consumers who come to visit and buy company products around 1210 consumers for 1 month and random sampling with the Slovin formula so that the number of research samples used is 92 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques using literature study, survey and observation. The data analysis technique is multiple linear regression, classical assumption test and hypothesis testing. The results showed that product quality and customer satisfaction partially and simultaneously had a positive and significant effect on consumer purchasing decisions for Garmin brand watch products. There is a strong correlation between product quality and customer satisfaction with consumer purchasing decisions on Garmin watch products. Consumer purchasing decisions can be explained by product quality and customer satisfaction by 46.50% and the remaining 53.5% can be explained by other variables not examined.